Professor Stefano Margaritora: my journey with uniportal VATS - He, Chao-Xiu (Melanie); Lun, Cliff (Video-Assisted Thoracic Surgery, 2017)
After 3 days’ course, the 4th International Uniportal VATS Course-Live Surgery and Wetlab had come to an end in Berlin on 4th March 2017. We were glad that Professor Stefano Margaritora, the head of Department of General Thoracic Surgery in Catholic University of Rome, Italy, had accepted the interview by our journal Video-Assisted Thoracic Surgery (VATS).